Test methods for electrical materials, printed boards and other interconnection structures and assemblies. Test methods for materials for interconnection structures. Measurement of resilience strength and resilience strength retention factor of flexible dielectric materials Part 2-501, (6th May 2022) - British Standards Institution,
No abstract available